Analisis Perbandingan Kinerja Keuangan Pada Bank Syariah Dan Bank Konvensional(Studi Kasus pada PT. Bank Syariah Mandiri dan PT. Bank Mandiri) - Ardyana, Vynna; , Drs. Atwal Arifin M.Si, Akt (2017)
This study aims to compare the financial performance of Sharia Commercial Banks with Conventional Commercial Banks in Indonesia in the period 2013-2016 using financial ratios. The financial ratios used consist of CAR, LDR, ROA, ROE, and BOPO. The data used in this research is obtained from Commercial Bank Publication Report 2006 to 2010 issued by each Bank concerned. After passing through the purposive sample stage, the sample is worthy of 2 samples, 1 Syariah Bank (Bank Syariah Mandiri) and 1 Conventional Commercial Bank (Bank Mandiri). The analytical technique used to compare the financial performance of Sharia Commercial Banks with Conventional Commercial Banks is the method of Independent sample t-Test. The analysis shows that there is a significant difference for each financial ratio between Sharia Commercial Bank and Conventional Commercial Bank in Indonesia. Sharia Commercial Banks perform better in terms of LDR and ROE ratios, while Conventional Commercial Banks perform better in terms of CAR, ROA, and BOPO ratios.